Static and Dynamic Experiment Evaluations of a Displacement Differential Self-Induced Magnetorheological Damper - Guoliang Hu; Wei Zhou; Mingke Liao; Weihua Li (Shock and Vibration)
This paper presents the development of a novel magnetorheological damper (MRD) which has a self-induced ability. In this study, a linear variable differential sensor (LVDS) based on the electromagnetic induction mechanism was integrated with a conventional MRD. The structure of the displacement differential self-induced magnetorheological damper (DDSMRD) was developed, and the theory of displacement differential self-induced performance was deduced. The static experiments of the DDSMRD under different displacement positions were carried out by applying sine excitation signals to the excitation coils, and the experimental results show that the self-induced voltage is proportional to the damper piston displacement. Meanwhile, the dynamic experiments were also carried out using the fatigue test machine to investigate the change of the self-induced voltage under the typical direct current inputs and the different piston rod displacements; the experimental results also show that the self-induced voltage is proportional to the damper piston displacements. Additionally, the dynamic mechanical performance of the DDSMRD was evaluated. The theory deduction and the experimental results indicate that the proposed DDSMRD has the ability of the integrated displacement sensor in addition to the output controllable damping force.